Stock Return Behavior and Its Fundamental Determinants: An Empirical Study in the COVID-19 Era - Muhammad Rofi’i (JURNAL ILMIAH EDUNOMIKA, 2026)
This study investigates the effect of profitability, liquidity, market value, and solvability on stock returns of firms in Indonesia during 2019–2023, a period marked by economic turbulence and recovery following the COVID-19 pandemic. The study further assesses the role of these financial indicators as market signals within the framework of signaling theory. Multiple linear regression analysis is applied to evaluate their respective impacts on stock returns. The results reveal that profitability, market value, and solvability do not significantly influence stock returns. In contrast, liquidity demonstrates a positive and significant effect. These findings indicate that, during periods of heightened economic uncertainty (COVID-19), investors prioritize liquidity as a reliable signal of financial stability, whereas other financial ratios lose explanatory power. This study provides novel evidence on how the informational value of financial indicators shifts during crisis periods. Unlike previous research conducted under normal economic conditions, the study highlights the diminished role of profitability-, earnings-, and leverage-based signals during the pandemic, offering new insights into investor behavior under extreme volatility. The findings offer practical guidance for investors, firms, and policymakers. Investors should emphasize liquidity metrics when evaluating firms during economic crises. Companies should enhance liquidity management and transparent financial communication. Policymakers may utilize these insights when designing market stabilization and corporate support programs in periods of economic disruption. Keywords: Fundamental Determinants, Stock Return; Signaling Theory; COVID-19.